A CASE REPORT OF PARACETAMOL-INDUCED TOXIC EPIDERMAL NECROLYSIS IN A FEMALE PATIENT AT A TERTIARY CARE HOSPITAL IN ASSAM - Purkayastha, Ayan; Chakravarty, Pinaki; Dewan, Babul (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Paracetamol is one of the most commonly available over the counter drug used for the treatment of fever. It is considered to be a relatively safe drug. However, some rare cases of Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) have been reported in the past which are thought to be associated with paracetamol use. Both SJS and TEN are severe hypersensitivity reactions and require prolonged hospitalization and intensive treatment. Here, we present the case of a 24-year-old female who developed TEN after taking two doses of paracetamol for fever. Keywords: Hypersensitivity, Paracetamol, Toxic epidermal necrolysis.